Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1021/jo020684o
|View full text |Cite
|
Sign up to set email alerts
|

UV Band Splitting of Chromogenic Azo-Coupled Calix[4]crown upon Cation Complexation

Abstract: Calixcrown-6 compounds carrying a pair of phenylazo moieties on the upper rim and two OH groups, one OH group, and two OR groups on the lower rim have been prepared in both the cone and partial cone conformations. UV/vis spectral measurements showed a red shift upon the addition of Ca2+ to the calixcrown carrying two OH groups and a blue shift for the calixcrown carrying two OR groups. For the compounds with two OR groups on the lower rim and a fixed partial cone conformation, a blue shift caused by electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 25 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…In another investigation, Kim et al 122 reported bifunctional (fluorogenic and chromogenic) calix[4]arene probes 50 and 51 (Figure 11). The (4-nitrophenyl)azo groups of these sensors were introduced as chromogenic moieties 123 to affect the nakedeye detection of F − ions. Probe 50 showed a characteristic fluorescence band at 480 nm originating from the excimer formed by the pyrene moieties.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…In another investigation, Kim et al 122 reported bifunctional (fluorogenic and chromogenic) calix[4]arene probes 50 and 51 (Figure 11). The (4-nitrophenyl)azo groups of these sensors were introduced as chromogenic moieties 123 to affect the nakedeye detection of F − ions. Probe 50 showed a characteristic fluorescence band at 480 nm originating from the excimer formed by the pyrene moieties.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…124). Their conformations were studied by 1 as potential chromogenic sensors [231]. They also wanted to investigate if there was any conformational dependence for the wavelength changes upon complex formation.…”
Section: Fluorescence/luminescencementioning
confidence: 99%
“…However, other specific methods include metal-catalyzed coupling [22][23][24], the oxidation of aromatic amines [25,26], reductive coupling of nitro aromatic compounds [26,27], conversion and reduction of aromatic N-oxides [28][29][30], catalytic coupling and thermal decomposition of aromatic azide compounds [31,32], and the catalytic coupling of aromatic diazonium salts [33][34][35][36]. However, these methods do not meet the requirements of green chemistry owing to the organic solvent and heavy metal ions in the reducing agent or antioxidant.…”
Section: Introductionmentioning
confidence: 99%